Antibacterial Halloysite‐Modified Chitosan/Polyvinylpyrrolidone Nanofibers for Ultrasensitive Self‐Powered Motion Monitoring - Si Wang; Bohao Liu; Xingdong Feng; Rui Pan; Yuanlingyun Cai; Renyan Zhang; Mingbo Pu; Xiaoliang Ma; Xiong Li; Huiling Tai; Xiangang Luo (Advanced Sensor Research, 2023)
Abstract High flexibility, porosity, and antibacterial activity are extremely desired for wearable health monitoring, which is beneficial to simultaneously promote wearing comfort and safety. In this study, an antibacterial nanofibers‐based triboelectric generator (AN‐TENG) composed of the flexible chitosan/polyvinylpyrrolidone modified with halloysite nanotubes (CTS/PVP/HNTs) nanofibers and cube‐arrays structured Ecoflex film is proposed for simultaneously energy harvesting and self‐powered human motion monitoring. The open‐circuit voltage (280 V), short‐circuit current (3.98 μA), and transferred charge (51 nC) of the CTS/PVP/HNTs nanofibers TENG at the optimal compound concentration are increased by 90.8%, 86.92%, and 96.2%, respectively, compared to the CTS/PVP nanofibers one (size: 3 cm × 3 cm, mechanical force: 10 N @1 Hz), revealing good real‐time monitoring ability for human wrist, elbow, and finger motion. An antibacterial test is carried out to evaluate the antibacterial activity and the antibacterial rate of the nanofibers against Escherichia coli (ATCC 8739) and Staphylococcus aureus (ATCC 6538) based on the current national standard GB/T 31402–2015, indicating good antibacterial properties of the nanofibers. This research offers an ingenious strategy to establish an antibacterial nanofibers‐based TENG for self‐powered motion monitoring and energy harvesting and offers a new insight to improve the practical security of wearable electronic devices.